Lipases as Tools in the Synthesis of Prodrugs from Racemic 9-(2,3-Dihydroxypropyl)adenine - Brabcová, J. (Jana); Blažek, J. (Jiří); Janská, L. (Lucie); Krečmerová, M. (Marcela); Zarevúcka, M. (Marie) (Molecules, 2012)
Lipases from Geotrichum candidum 4013 (extracellular lipase and cell-bound lipase) were immobilized by adsorption on chitosan beads. The enzyme preparations were tested in the synthesis of ester prodrugs from racemic 9-(2,3-dihydroxypropyl)adenine in dimethylformamide with different vinyl esters (acetate, butyrate, decanoate, laurate, palmitate). The transesterification activities of these immobilized enzymes were compared with commercially available lipases (lipase from hog pancreas, Aspergillus niger, Candida antarctica, Pseudomonas fluorescens).